VIDEO DOKUMENTER WISATA KABUPATEN DHARMASRAYA - Sindi Septiani; hendra afriwan (Universitas Negeri Padang, 2020)
The design of a tourist documentary video for Dharmasraya Regency, West Sumatra Province, aims to increase the number of visitors who are still small due to the ineffective use of promotional media. The author is interested in raising this problem and designing a final work entitled